Primitive neuroectodermal tumor (PNET) of the lung in an adult woman - Gachechiladze, Mariam; Skarda, Josef; Ibrahim, Maha; Tichý, Tomáš; Flodr, Patrik; Latálová, Pavla; Ehrmann, Jiří; Trojanec, Radek; Kolář, Zdenek (World journal of surgical oncology, 2014)
Primary primitive neuroectodermal tumors (PNETs) are extremely rare in the lung and especially in adult women. We describe a case of PNET of the lung with aggressive behavior in 31-year-old woman. Diagnosis was based on histopathological and immunohistochemical studies, and confirmed by molecular genetic analysis of chromosome rearrangements in the EWSR1 gene region. Clinical follow-up, post-mortem findings, and differential diagnosis are also discussed.
Keywords: diferenciální diagnóza; primitivní neuroektodermové nádory; Diagnosis, Differential; ženské pohlaví; nádory plic; protinádorové látky; dospělí; Humans; Adult; lidé; Anemia; Female; Fatal Outcome; Antineoplastic Agents; Neuroectodermal Tumors, Primitive; Lung Neoplasms; fatální výsledek; anemie